Molecular Mechanics Simulations Of Quartz Etching Process - Abdul Manap, Abdul Haadi (2016)

(untitled)
In this thesis, the physical etching of argon bombardment onto α-quartz and amorphous quartz substrates were studied and investigated using molecular mechanics methods. Although there are extensive studies on quartz etching, larger numbers of the research are experimental and the studies focus on the process outcomes rather than the fundamental study of the process. Molecular mechanics methods such as Monte Carlo (MC) method and Molecular Dynamics (MD) method enables researchers in building the model from ground up to the physical etching process. This kind of bottom-up design allows us to study the process in molecular level and help researcher grasp the fundamental theory of the process. Two computational methods have been employed in order to study quartz etching process. The first method are based on statistical approach i.e Monte Carlo and the second method is based on deterministic approach i.e Molecular Dynamics. In Monte Carlo method, the main interest of the simulations is sputtering yield, Ys and energy distribution of sputtered atoms. The relationship of incident energy, Ei , and incident angle θi to the interested subjects will also been investigated and discussed. It was found that at incident angle θi =70⁰ at any incident energy, Ei, the sputtering yield, Ys is maximum. Molecular Dynamics method reported the effect of etching selectivity, the effect of substrate temperature, Ts, and the effect of incident energy, Ei to the sputtering yield and ultimately corroborates the factor and sputtering yield with the properties of the substrate. The main objective of this project is to use computational method (i.e Molecular Dynamics) to model the process at the scale of molecular level. Two difference substrates (amorphous and α-quartz) are subjected to a range of incident energy. Ei and temperature, Ts and the sputtering yield were studied. Morse potential and Second Generation Charge-Optimized Many Body (COMB) potentials were utilised as the inter-atomic potential. α-quartz shows higher sputtering yield as compared to amorphous quartz at any given incident energy, Ei and substrate temperature, Ts. α-quartz has also produced more stoichiometric yield compared to amorphous quartz. This is because for α quartz, the sputtered product are in mostly the form of SiO2 molecule while amorphous substrate the sputtered product in the form of atom. Incident enery, Ei gave significant increase in the sputtering yield compared to temperature, Ts. In this thesis, the computational model of physical etching on quartz has been demonstrated using the Monte Carlo (MC) method and Molecular Dynamics (MD) method. Several factors are studied and better understandings of the process in molecular level have been achieved. The results of this study could be applied in 2D and 3D patterning used in lithography technique